Botany in Portuguese textbooks: Analysis of seven Biology books for High School students - Santos, Fernando Santiago dos (2019)
Botany has traditionally been considered one of the most neglected areas in Biology, although it is of high importance for the environment, daily life, economy and so forth. This paper analysed how botanical contents are displayed in high-school textbooks used in Portugal for 10th, 11th and 12th grades. The methodological procedures are based on content analysis with a posteriori nine categories and sub-categories: i) Figures, ii) Additional information boxes, iii) Language, iv) Concepts, v) Contextualization, vi) Activities, vii) History of Science and Technology, viii) Teacher’s guidebook, and ix) Transversal topics. An overview of our analysis has evidenced that the Portuguese textbooks studied lack contextualization and perhaps deeper relations with other areas of knowledge, despite language is used correctly and appropriately in all books, and teachers’ guide books are precise and adequate. Textbook analyses are important tools to track the way Science is dealt with by students and teachers.